Development of a CRISPR-Cas9 Tool Kit for Comprehensive Engineering of Bacillus subtilis - Westbrook, A. W.; Moo-Young, M.; Chou, C. P. (Applied and Environmental Microbiology, 2016)
The establishment of a clustered regularly interspaced short palindromic repeat (CRISPR)-Cas9 system for strain construction in Bacillus subtilis is essential for its progression toward industrial utility. Here we outline the development of a CRISPR-Cas9 tool kit for comprehensive genetic engineering in B. subtilis. In addition to site-specific mutation and gene insertion, our approach enables continuous genome editing and multiplexing and is extended to CRISPR interference (CRISPRi) for transcriptional modulation. Our tool kit employs chromosomal expression of Cas9 and chromosomal transcription of guide RNAs (gRNAs) using a gRNA transcription cassette and counterselectable gRNA delivery vectors. Our design obviates the need for multicopy plasmids, which can be unstable and impede cell viability. Efficiencies of up to 100% and 85% were obtained for single and double gene mutations, respectively. Also, a 2.9-kb hyaluronic acid (HA) biosynthetic operon was chromosomally inserted with an efficiency of 69%. Furthermore, repression of a heterologous reporter gene was achieved, demonstrating the versatility of the tool kit. The performance of our tool kit is comparable with those of systems developed for Escherichia coli and Saccharomyces cerevisiae, which rely on replicating vectors to implement CRISPR-Cas9 machinery. IMPORTANCE In this paper, as the first approach, we report implementation of the CRISPR-Cas9 system in Bacillus subtilis, which is recognized as a valuable host system for biomanufacturing. The study enables comprehensive engineering of B. subtilis strains with virtually any desired genotypes/phenotypes and biochemical properties for extensive industrial application.